EXPERIMENTAL TRANSPLANTATION OF THE CLAM MERETRIX CASTA (CHEMNITZ) IN THE MARINE FISH FARM - Durve, V S (Indian Journal of Fisheries, 2011)
Several hundred clams, Meretrix casta (Chemnitz) obtained from Athankarai estuary (Long- 79Â°E, Lat. 9Â° ICN.) on 28th Ostobjr, 1964, were transplanted in the pond of the flsh farm of the Central Marine Fisheries Research Institute, Mandapam Camp- During the period of study extending over six months, it was found that there was an initial high rate of growth in the seed clams immjdiately on transplantation. However, this rate of growth declined first slowly and then rapidly after five months. Probable causes for this uneven growth are discussed